Updated Evidence and Policy Developments on Reducing Gun Violence in America - Vernick, Jon S.; Webster, Daniel W. (Book collections on Project MUSE., 2014)
"In 2013--in the wake of the tragic shooting at Sandy Hook Elementary School--Johns Hopkins University Press published Reducing Gun Violence in America, a collection of essays written by the world's leading experts on gun violence. Updated Evidence and Policy Developments on Reducing Gun Violence in America follows up on the state of American gun violence by analyzing new data, research, and policy developments one year after Sandy Hook. Over the course of ten substantive chapter addendums, contributors bring readers up-to-date on such varied topics as mental illness, domestic violence, background checks, illegal gun sales, and personalized guns. They describe the recent policy measures that have been enacted and suggest additional approaches that may help stem the violence. An essential companion to Reducing Gun Violence in America, the reliable, empirical research and legal analysis in this e-book will help lawmakers, opinion leaders, and concerned citizens identify policy changes to address gun violence, which takes an average of more than 80 lives every day in the United States"--Publisher's description